2007
DOI: 10.1142/s0218271807011152
|View full text |Cite
|
Sign up to set email alerts
|

Shift of the Isco and Gravitomagnetic Clock Effect Due to Gravitational Spin–orbit Coupling

Abstract: Considering a gravitational coupling between the spin and the orbital angular momentum of a spinning test particle orbiting a central massive body, we derive two particular consequences: (1) the influence of the coupling on the location of the innermost stable circular orbit and (2) the gravitomagnetic clock effect due to this coupling. The previous result does not seem to exist for the former, while for the latter we arrive at a result that coincides with what we think is the most accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The ISCO in different black holes have been investigated in refs. [36][37][38][39][40][41][42][43][44][45]. According to [46], all spherical orbits are not bounded of the black hole.…”
Section: Isco and Mbcomentioning
confidence: 99%
“…The ISCO in different black holes have been investigated in refs. [36][37][38][39][40][41][42][43][44][45]. According to [46], all spherical orbits are not bounded of the black hole.…”
Section: Isco and Mbcomentioning
confidence: 99%
“…Previous to these theoretical advancements, the dynamics of a non-spinning particle moving on a geodesic around a Schwarzschild BH was first studied by Kaplan in [15]. Since then the dynamics of non-spinning particles has been studied vastly by researchers [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The study of non-spinning particles in the vicinity of different BHs showed that the motion of the massive or massless test particles gets affected by the BHs parameters like mass, charge and rotation.…”
Section: Introductionmentioning
confidence: 99%
“…and obtain the differentiate between prograde and retrograde orbits and integrate from zero to 2π. The clock effect is the difference of theses two orbits [8], [9], [10]. The fourth group takes some elements of electromagnetism and does an analogy between Maxwell equations and Einstein linealized equations [11], [12], [13], [14], [15], [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…and obtain the differentiate between prograde and retrograde orbits and integrate from zero to 2π. The clock effect is the difference of theses two orbits [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation